Sengketa Gugatan Perdata atas Kepemilikan Tanah Istana Negara Tampaksiring Oleh Masyarakat di Desa Manukaya Gianyar - I Nyoman Sukrata; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2022)
The government expanded the area of ​​the Tampaksiring State Palace and housing for Presidential Palace employees that had been acquired by the state and privately owned land in Manukaya Village. The purpose of this research was to determine the process of land ownership disputes at the Tampaksiring State Palace and to analyze the obstacles faced in resolving disputes over land ownership of the Tampaksiring State Palace by the people in the village of Manukaya. The research method used is Empirical Law. This research uses: a sociological approach, a statutory approach, and a fact approach in conducting research. Primary data comes from the results of field interviews which are then linked to legislation relevant to the case in the field and secondary data comes from: law books and legal journals that support primary data. Interview techniques were carried out as research data collection, library research techniques, and observation. The disputed land belonging to the Plaintiffs which was released by the Government was used as Housing for the employees of the Tampaksiring Presidential Palace at the time of release, the proof of ownership was still in the form of Girik/details of the 1948 Klasiran and Petok D. In the trial it turned out that the government, in this case the Tampaksiring State Palace, was able to prove it with evidence: Letter of application for Rights Use, dated January 27, 1986. Therefore, the community should first check the completeness of the evidence along with the certificate and the government should also increase efforts to prevent land disputes between the parties.